O discurso da justiça como equidade: significados contraditórios em conflito - Pereira, Ana Paula (Universidade Federal de São Carlos, 2010)
Our research examined the question of the meanings of Justice; Do we live in a social group where Justice has the fundamental principle of equity among all of its participants? Is this notion of equity an eternal truth? Perhaps it is only an idealism in language or an idealism of the laws which control our social organisations? Exploring the meanings of Justice, our focus was on speech construction, developed by the magazines Veja and Isto é when they reported on the Primeiro Comando da Capital in May 2006.Our objective was to examine how social groups recognise and value themselves at times of social instability. Do all the members of the social group consider themselves as equals? Our epistemology was Dialogism, developed by the Russian philosopher, Mikhail Bakhtin. Using his methodology we identified in the corpus, the construction of two speech genres: one creating fear, and the other, pedagogic. On the one hand, the magazine reports displayed the development of a speech full of fear for the destabilisation of the dominant social group s order. We also identified the construction of a pedagogic speech which instructed the State to resolve the problems from social destabilisation. In both speech genres, we identified the presence of ideologies which indicated the lack of social equity among all the members of the group.
Keywords: Dialogismo; Bakhtin, Mikhail Mikhailovitch, 1895-1975; LINGUISTICA, LETRAS E ARTES::LINGUISTICA